Effects of gender and income on Malaysian’s financial capability - Sabri, Mohamad Fazli; Mokhtar, Nuradibah; Ho, Catherine Soke Fun; Anthony, Mervin; Wijekoon, Rusitha (Malaysian Consumer and Family Economics Association, 2020)
The rapidly changing world and financial landscape have resulted in the availability of newer and more attractive financing alternatives, thus attracting the attention of households and resulting in the increasing debt levels in developed and emerging countries alike. This is a worrying trend and nations are scrambling to ensure that their consumers are well-equipped with the knowledge and practice of financial capability to prevent the problem of overreliance on debt and welfare, as well as to enhance financial health sustainability. Therefore, this study aimed to reveal the impact of sociodemographic characteristics on the four domains of financial capability, namely planning ahead, managing money, choosing products, and staying informed. A self-administered questionnaire was distributed to a sample of 2000 respondents across Malaysia, whereby data analysis revealed that gender posed a significant effect on the domains of planning ahead and staying informed. In contrast, income did not affect financial capability. Thus, it is recommended that greater attention should be placed on research and professional training towards building one’s financial capability. Furthermore, both the government and non-governmental organisations should develop an inclusive approach to increase the financial capability and upgrade the living standards of especially-financially-vulnerable households.